Chemical, electronic and nanostructural properties of nanocrystalline silicon synthesised by hot‐wire CVD. Issue 7 (20th April 2016) - Oliphant, Clive; Arendse, Christopher; Pepenene, Refuoe; Cummings, Franscious; Kruger, Oelof; Jordaan, Werner; Muller, Theo
Abstract : This study examines the correlation between the chemical, electronic and optical properties of a nanocrystalline silicon thin film fabricated by hot‐wire chemical vapour deposition. The locations of porosity and the incubation layer of the thin film can be monitored by tracking the SiH2 and SiH signals, respectively, from time of flight secondary ion mass spectrometry. High resolution transmission electron microscopy shows that the mean nanocrystallites size is larger along the growth direction. Electron energy loss spectroscopy reveals a reduction in the intensity of the Si L‐edges spectra, i.e. reduced transitions from the silicon 2p band to the conduction band, within the incubation layer and a subsequent recovery thereafter moving along the crystalline cone regions. Despite the presence of porosity, the oxygen within the nanocrystalline silicon thin film is predominately at the surfaces of the film and the interface region with the crystalline silicon substrate. Knowledge of these evolving features of the nanocrystalline silicon thin film were then taken into consideration during the construction of an optical model based on the effective mass approximation, which then allows for the accurate determination of the film thickness based on basic UV–Vis spectroscopy.